2020
DOI: 10.1088/1757-899x/722/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Risk mitigation on product distribution and delay delivery : A case study in an Indonesian manufacturing company

Abstract: In a dynamic supply chain environment, problems that arise due to delays in the delivery of raw materials and distribution of products to consumers can pose risks and threats to the company. This study aims to identify and mitigate the risk of late delivery of goods. Risk management starts with identifying sources of risk, defining risks, creating risk maps and mitigating risks. a case study conducted at a manufacturing packaging company in Batam, Indonesia. The results showed that the biggest risks were suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…The interview sessions with the participants revealed that INACCURATE INFORMATION significantly affects ontime delivery. This finding is consistent with the findings of other scholars, such as Kusrini et al (2020) and Marpaung (2021), who identified precision and accuracy as areas requiring mitigation to improve the on-time delivery of export items. Most participants in the study also agreed that INACCURATE INFORMATION significantly causes late delivery in the company.…”
Section: Causes Illustrated In Ansupporting
confidence: 92%
See 2 more Smart Citations
“…The interview sessions with the participants revealed that INACCURATE INFORMATION significantly affects ontime delivery. This finding is consistent with the findings of other scholars, such as Kusrini et al (2020) and Marpaung (2021), who identified precision and accuracy as areas requiring mitigation to improve the on-time delivery of export items. Most participants in the study also agreed that INACCURATE INFORMATION significantly causes late delivery in the company.…”
Section: Causes Illustrated In Ansupporting
confidence: 92%
“…Due to this constraint, there is often a need to record the order transaction using manual methods, forms, or other alternative systems. The present finding aligns with the studies by Kusrini et al (2020) and Obiero (2019). Both studies suggest that optimal integration of information technology is crucial for enhancing information sharing, which is crucial in addressing the issue of late delivery of export items within the food trading company.…”
Section: Causes Illustrated In Ansupporting
confidence: 91%
See 1 more Smart Citation
“…XYZ to overcome the case of delay delivery owned by the company. According to research of Kusrini [2] , there are several factors that cause delay delivery, one of which is the FG transfer factor. This FG transfer factor is triggered by three other factors, which is planning, quality check, and material order.…”
Section: Fig 1 Grafik Delay Delivery Jan -Apr 2022mentioning
confidence: 99%